Peripherally Crowded Cationic Phthalocyanines as Efficient Photosensitizers for Photodynamic Therapy - Halaskova, Marie; Rahali, Asma; Almeida-Marrero, Verónica; Machacek, Miloslav; Kucera, Radim; Jamoussi, Bassem; Torres, Tomás; Novakova, Veronika; de la Escosura, Andrés; Zimcik, Petr (ACS medicinal chemistry letters, 2021)
Photodynamic therapy is a treatment modality of cancer based on the production of cytotoxic species upon the light activation of photosensitizers. Zinc phthalocyanine photosensitizers bearing four or eight bulky 2,6-di(pyridin-3-yl)phenoxy substituents were synthesized, and pyridyl moieties were methylated. The quaternized derivatives did not aggregate at all in water and retained their good photophysical properties. High photodynamic activity of these phthalocyanines was demonstrated on HeLa, MCF-7, and EA.hy926 cells with a very low EC50 of 50 nM (for the MCF-7 cell line) upon light activation while maintaining low toxicity in the dark (TC50 ≈ 600 μM), giving thus good phototherapeutic indexes (TC50/EC50) above 1400. The compounds localized primarily in the lysosomes, leading to their rupture after light activation. This induced an apoptotic cell death pathway with secondary necrosis because of extensive and swift damage to the cells. This work demonstrates the importance of a bulky and rigid arrangement of peripheral substituents in the development of photosensitizers.